PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI DAN BUDAYA ETIS ORGANISASI TERHADAP KECURANGAN AKUNTANSI DI PT HUADI NICKEL ALLOY INDONESIA - Weinberg Janne Trisnawaty AP; Andry Arifian Rachman (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to examine and analyze the influence of internal control effectiveness, compensation appropriateness, and organizational ethical culture on accounting fraud at PT Huadi Nickel Alloy Indonesia. The research method used in this study is a causal comparative method, aimed at investigating the cause-and-effect relationships between the variables studied. This study employs a quantitative approach using primary data obtained from the distribution of questionnaires to employees selected based on specific criteria. The sampling technique applied is purposive sampling. The population of this study comprises 60 individuals, from which 52 respondents were obtained. The questionnaire in this study uses a likert scale offering five response options with scores ranging from 1 to 5. The data analysis method used is multiple linear regression, with testing carried out using the IBM SPSS Statistics software. The results of this study indicate that internal control effectiveness and organizational ethical culture don’t significantly influence accounting fraud. On the other hand, compensation appropriateness has a significant but positive effect, which contradicts the initial hypothesis of this study. Therefore, the assumption that compensation appropriateness negatively affects accounting fraud is not supported. Keywords: Internal Control, Compensation Appropriateness, Organizational Ethical Culture, Accounting Fraud